PENGARUH PELAKSANAAN PROMOSI TERHADAP TINGKAT PENJUALAN PRODUK TABUNGAN PADA PT. BANK RIAU KEPRI CABANG UTAMA PEKANBARU - Winda Zainur; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted in PT. Bank Riau Kepri Cabang Utama Pekanbaru.. The setting of the problem is the effect of the implementation of sales promotion to the level of savings products at PT. Bank Riau Kepri Cabang Utama Pekanbaru.. The purpose of this research is to investigate the implementation of promotions, product sales, and determine the effect of the implementation of sales promotion to the level of savings products at PT. Bank Riau Kepri Cabang Utama Pekanbaru.This research using descriptive quantitative analysis method with SPSS system,questionaire used for collect the data, sampling technic using accidental sampling. This research composed of primery data and secondary data which is collected by writer from PT. Bank Riau Kepri Cabang Utama Pekanbaru. The result of this research shown that the implementation of sales promotion is influenced significantly to the level of savings products at PT. Bank Riau Kepri Cabang Utama Pekanbaru..Keywords : implementation of sales promotion, the level of savings products,savings product